Pleomorphic hyalinizing angiectatic tumor of breast - Alaa A. Salim; Abdulhadi Samman; Ali Hassan Assiri (Human Pathology: Case Reports, 2020)
Pleomorphic hyalinizing angiectatic tumor (PHAT) is a rare soft tissue tumor of uncertain histogenesis that was initially described in 1996. The tumor has a strong predilection for the subcutaneous soft tissue of the distal extremities with handful number of cases reported in other locations. Here, we report a case of PHAT involving the breast soft tissue of a 61-year-old man, who presented with a painless left breast mass slowly growing over the period of 4 years. Core needle biopsy was performed to rule out malignancy. The biopsy showed several ectatic hyalinized blood vessels, surrounded by mitotically inactive spindled to pleomorphic cells embedded in a fibromyxoid stroma. The tumor had strong immunohistochemical expression of CD34, CD99 and Bcl2, while being negative for S100, cytokeratin, actin and desmin. The features were consistent with PHAT. This was followed by a wide local excision with no documented recurrence or metastasis 36 months after surgery. This case is reported to increase the awareness of this entity to be considered in the differential diagnosis of pleomorphic and spindle cell tumors of the breast seen on core biopsies to avoid misdiagnosis and unnecessary radical surgical procedures.